Bioengineered stem cell membrane functionalized nanocarriers for therapeutic targeting of severe hindlimb ischemia. (December 2018) - Bose, Rajendran JC.; Kim, Byoung Ju; Arai, Yoshie; Han, In-bo; Moon, James J.; Paulmurugan, Ramasamy; Park, Hansoo; Lee, Soo-Hong
Abstract: Bioengineering strategies to enhance the natural targeting function of nanocarriers would expand their therapeutic applications. Here, we designed bioengineered stem cell membrane-functionalized nanocarriers (BSMNCs) harboring C-X-C chemokine receptor type 4 (CXCR4) to achieve robust targeting and also to increase their retention time in ischemic tissue. Stem cell membrane coated nanocarrier (SMNCs) or poly (lactic- co -glycolic acid) (PLGA) nanocarriers (PNCs) and BSMNCs were prepared by functionalizing PNCs with human adipose-derived stem cells (hASCs) membranes and hASCs engineered to overexpress CXCR4-receptor, respectively. The functionalization of PNCs with stem cell membranes derived from hASCs significantly enhance the nanocarrier penetration across endothelial cell barrier compare to PNCs. In addition, stem cell membrane functionalization on PNCs also significantly decreased the nanoparticles uptake in J774 (murine) and THP (human) macrophages respectively from 84% to 76%–29% and 24%. Interestingly, BSMNCs showed much higher level of accumulation in ischemic tissue than SMNCs. Systemic retro-orbital injection of BSMNCs loaded with VEGF into mice with hindlimb ischemia resulted substantially enhancement of blood reperfusion, muscle repair, and limb salvage compared to animals treated with SMNCs loaded with similar concentration of VEGF. The reported strategy could be used to create biocompatible and custom-tailored biomimetic nanoparticles with various hybrid functionalities, which may overcome the limitations of current nanoparticle-based therapeutic and imaging platforms.